Design and Use of Quickappninja-Based Android Games in Mathematics Learning Through Google Meet - Dharma Atmaja, I Made (Journal of World Science, 2022)
One of the platforms that can be used for online learning is Google Meet, which is a product made by Google. Google Meet can replace the conventional form of class into an interactive virtual class. The use of quickappninja-based android games in learning mathematics through Google Meet is a medium that can make learning more varied and interesting. Quickappninja is a device in the form of web pages that can be accessed online to create android games using HTML language. Using Quickappninja is easy because it does not require a programming language. In making android games through quickappninja, teachers will be more flexible in developing games according to their needs and subject matter. Apart from being delivered classically through Google Meet, this android game can also be used independently for students as a medium of learning at home, as well as repetition of material for students so that they can better understand math subject matter.